Development of Cost Analysis Guidance for Indonesian Hospitals - Ragil Setia Dianingati; Arthorn Riewpaiboon (Faculty of Pharmacy, Universitas Gadjah Mada)
Health technology assessment is important in the process of national health insurance system development. On the other hand, health technology assessment study needs a cost analysis as a basic, which is a troublesome if there is not any guidance. To help performing the cost analysis study, this study describes the development of a costing manual book and template as a guide for costing analysis in Indonesian hospitals. This management tool developed in stages, from tool drafting, testing in the real life environment, to approval from stakeholders. Costing templates were developed using Microsoft Excel formulas, such as IF, SUMIF and TRANSPOSE. The costing manual book and template were designed for the Indonesian hospital context. The costing template successfully assessed the unit costs of healthcare services in the study hospital. It can calculate the unit costs of healthcare services for 3 main objectives: hospital internal management, reimbursement rate setting and economic evaluation. The costing analysis tool was reviewed and approved by the study hospital staff and stakeholders. Even the model test was only tested in one district hospital, but it was designed to be flexible enough to adapt to different hospital organization structures. The cost analysis guidance is relevant and applicable to district hospitals in Indonesia. It is well accepted by stakeholders and helpful in calculating the hospital unit costs in a practical way. Hopefully, there will be further hospital cost analyses in the future. These cost analyses can then be used as inputs for universal health coverage development.